Analisis Hukum Bunga Kredit Usaha Rakyat (KUR) pada Kantor Cabang Pembantu (KCP) BRI Unit Kamal Bangkalan Ditinjau dari Perspektif Maqashid Syariah - Rozi, Iqbal Fakhrur; Qadariyah, Lailatul (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Kredit Usaha Rakyat (KUR) is a debt scheme with a low interest rate provided to small and medium enterprises (MSMEs) that require additional capital and credit for business development. Bank BRI Kamal Unit, as one of the KUR distributors, has successfully implemented this program with a value of 5.5 billion rupiah in 2022. However, from a sharia perspective and based on the opinions of scholars, whether the KUR program with an interest component that is forbidden in Islam can be said to be usury or can be said to be halal if someone is forced to do so, remains to be seen. So the purpose of this research aims to analyze the law of KUR interest through the views of scholars who state that it is haram, halal, or even syubhat in terms of the maqashid sharia perspective. This type of research is descriptive qualitative, where attention is paid to current issues during the research. Through descriptive qualitative research, researchers try to describe events and events in focus without special treatment. The last stage in data analysis is drawing conclusions and verification. As a result, it is known that the view of scholars who allow KUR loans is more in line with Maqasid Sharia, namely the preservation of life (hifz al-nafs) and property (hifz al-mal), compared to its prohibition, both of which are placed at the Dharuriyyat level or at least Hajiyyat. Keywords: Interest, KUR, Riba, Maqashid Syariah